Developing Assessment Instrument as a Mathematical Power Measurement - Imam Kusmaryono; Hardi Suyitno; Dwijanto Dwijanto; Nurkaromah Dwidayati (Journal of Education and Learning (EduLearn), 2018)
This was a field research (literature review and exploration) with descriptive quantitative approach. This study aims: (1) to develop a model (scheme) to assess mathematical power, (2) to test the validity of instruments of mathematical power assessment, and (3) to developa valid and reliable test and non-test instrument prototypes as a mathematical power measurement. The research instruments consist of 4 items of essay test, 20 sheets of observation on investigative activities, and 20 items of questionnaires. Validity test was conducted through constructions built up from 3 aspects of mathematical power ability. Result of instrument analysis showed that: (1) the r of instrument test = 0.947, meaning that the instrument is reliable, (2) the r of activity observation sheets = 0.912, meaning that the instrument is reliable, and (3) the r of questionnaires = 0.770, meaning that the questionnaire is reliable on 0.05 significance level. This study concludes: (a) the steps in the model (scheme) of mathematical power assessment may be used as a reference for assessing mathematical power, (b) test and non-test instruments are valid and reliable, and (c) prototypes of test and non-test instruments may be used as a measurement in mathematical power assessment.